Amphiphilic and Biocompatible DNA Origami‐Based Emulsion Formation and Nanopore Release for Anti‐Melanogenesis Therapy. Issue 45 (4th October 2021) - Huang, Hao; Belwal, Tarun; Li, Li; Xu, Yanqun; Zou, Ligen; Lin, Xingyu; Luo, Zisheng
Abstract: Programmable engineered DNA origami provides infinite possibilities for customizing nanostructures with controllable precision and configurable functionality. Here, a strategy for fabricating an amphiphilic triangular DNA origami with a central nanopore that integrates phase‐stabilizing, porous‐gated, and affinity‐delivering effects is presented. By introducing the DNA origami as a single‐component surfactant, the water‐in‐oil‐in‐water (W/O/W) emulsion is effectively stabilized with decreased interfacial tension. Microscopic observation validates the attachment of the DNA origami onto the water‐in‐oil and oil‐in‐water interfaces. Furthermore, fluorescence studies and molecular docking simulations indicate the binding interactions of DNA origami with arbutin and coumaric acid at docking sites within central nanopores. These central nanopores are functionalized as molecular gates and affinity‐based scaffold for the zero‐order release of arbutin and coumaric acid at a constant rate regardless of concentration gradient throughout the whole releasing period. In vivo zebrafish results illustrate the advantages of this zero‐order release for anti‐melanogenesis therapy over direct exposure or Fickian diffusion. The DNA origami‐based W/O/W emulsion presents anti‐melanogenic effects against UV‐B exposure without cardiotoxicity or motor toxicity. These results demonstrate that this non‐toxic amphiphilic triangular DNA origami is capable of solely stabilizing the W/O/W emulsion as well as serving as nanopore gates and affinity‐based scaffold for constant release. Abstract : Customized amphiphilic triangular DNA origami with a central nanopore successfully attaches onto the water‐in‐oil and oil‐in‐water interfaces as a single‐component surfactant to solely stabilize the water‐in‐oil‐in‐water emulsion. The nanopores with specific binding interactions are functionalized as nano‐porous gated materials for the zero‐order release of arbutin and coumaric acid for anti‐melanogenesis therapy.